Dominação local e padrão de liderança: disputa política e organização partidária na província do Maranhão (1840/1857) - Santos, Arthur Roberto Germano (2022)
This paper address two distinct but related questions: identify how the provincial political elite is configured based on information from the Provincial Assembly and debates in the press of the time; and identify the formation and organization of local political groups that congregated around certain interests, perspectives, and identities. This will allow us to question the current historiographical hypothesis that local political groups / parties were not formed following a leadership pattern, exercising command as an auxiliary, secondary activity. First, the article looks at the composition of the Provincial Assembly to verify if there were groups engaged in the ‘occupation of politics.’ Then, it addresses a key point to understand the organization of Maranhão’s political groups: the repeated reference to the local party organization and its transformations. In this regard, the analysis focuses on the formation of the Liga Liberal Maranhense, an agglutination of dissidents from the two main parties in the Maranhão province: the cabanos (saquaremas/conservatives) and bemtevis (luzias/liberals). This paper seeks to demonstrate that its formation, in 1846, is fundamental to understanding Maranhão’s political groups.